2012
DOI: 10.3109/00498254.2012.734642
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability, metabolism and disposition of oral pazopanib in patients with advanced cancer

Abstract: 1. Pazopanib (Votrient) is an oral tyrosine kinase inhibitor that was recently approved for the treatment of renal cell carcinoma and soft tissue sarcoma. 2. In this two-part study, we investigated the metabolism, disposition of [(14)C]pazopanib, and the oral bioavailability of pazopanib tablets in patients with advanced cancer. 3. In part A, three men each received a single oral dose of [(14)C]pazopanib in suspension (400 mg, 70 µCi). Pazopanib was the predominant drug-related component in circulation. Two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 8 publications
1
59
0
Order By: Relevance
“…The disparity between expression level and metabolic activity of CYP3A4 could be due to its functional regulation at post-trascriptional level3940. Notwithstanding these differences, we anticipate that HLCs from all five patient-specific iPSC lines will be capable of metabolizing PZ as CYP3A4 and CYP1A2 activities primarily mediate metabolism of PZ30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparity between expression level and metabolic activity of CYP3A4 could be due to its functional regulation at post-trascriptional level3940. Notwithstanding these differences, we anticipate that HLCs from all five patient-specific iPSC lines will be capable of metabolizing PZ as CYP3A4 and CYP1A2 activities primarily mediate metabolism of PZ30.…”
Section: Resultsmentioning
confidence: 99%
“…PZ belongs to the class of tyrosine kinase inhibitor drugs, several among which are known to be metabolized to reactive intermediates partially accounting for their toxicity profiles29. However, for PZ no reactive metabolites have been identified in patients30, and pharmacogenetic analyses have yielded weak associations with two genetic markers HFE 31 and UGT1A1 32 for elevated ALT and bilirubin levels, respectively. The high incidence of hepatotoxicity, the obscure mechanism underlying this and the paucity of biomarkers for predicting hepatotoxicity, prompted the choice of PZ as the drug to demonstrate the utility of patient-specific HLCs for modeling idiosyncratic hepatotoxicity.…”
mentioning
confidence: 99%
“…Pazopanib as monotherapy given orally at 800 mg once daily is approved for the treatment of advanced renal cell carcinoma, soft tissue sarcoma and currently under investigation in multiple tumour types [2][3][4][5][6]. Pazopanib exhibits high inter-individual variability mainly due to its pharmacokinetic properties: low bioavailability (ranging from 14 to 39 % [7]), oxidative metabolism by CYP3A4 and substrate of P-glycoprotein and Breast Cancer Resistance Protein. Several studies have demonstrated pharmacokinetic/pharmacodynamic (PK/PD) relationships, suggesting that therapeutic drug monitoring (TDM) of pazopanib would be useful for individualized dosing of this drug [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Pazopanib is another multikinase inhibitor that provides both therapeutic effect and favorable tolerability . It is metabolized mainly by CYP3A4, with CYP1A2 and CYP2C8 contributing to a smaller extent, to form its metabolites (M1–M7) . Only the M2 (GSK1268997) metabolite has a bioactivity similar to pazopanib.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%